Circadian variation in clinical features and outcome of intracerebral hemorrhage: The INTERACT studies. (20th October 2016) - Zheng, Danni; Sato, Shoichiro; Cao, Yong-Jun; Arima, Hisatomi; Carcel, Cheryl; Chalmers, John; Anderson, Craig S.
ABSTRACT: Previous studies consistently reported a diurnal variation in the occurrence of intracerebral hemorrhage (ICH), with a morning peak. However, limited knowledge exists on the circadian pattern of ICH severity and outcome. This study aimed to determine possible associations between ICH onset time and admission severity and 90-day outcomes using the combined data set of the pilot and main-phase Intensive blood pressure (BP) reduction in an acute cerebral hemorrhage trial (INTERACT). The ICH onset time was categorized into three groups (1: 00:00–07:59; 2: 08:00–15:59; and 3: 16:00–23:59). We found an association between onset time and low Glasgow Coma Scale score: aOR (time 1: 1.72, 95% CI 1.12–2.66; time 3: 1.95, 95% CI 1.31–2.89, p = 0.003; in comparison to time 2). There was no association between onset time and volume of ICH (adjusted p = 0.354) or 90-day outcomes of death or major disability, and death and major disability separately (all adjusted p > 0.4). The results showed that more severe cases of ICH patients, defined by a reduced level of consciousness, had late afternoon to early morning stroke onset, but this was unrelated to baseline hematoma volume or location. There was no circadian influence on ICH clinical outcome.